IMPLEMENTASI AYUNAN MEKANIS MENGGUNAKAN INDIKATOR FREKUENSI DAN INTENSISTAS SUARA TANGISAN BAYI PADA PLANT SMART INKUBATOR BAYI MENGGUNAKAN LOGIKA FUZZY DENGAN METODE MAMDANI - Robintang Sotardodo Situmorang; n/a Rahmadwati; Moch. Rusli (Jurnal Mahasiswa TEUB, 2023)
An incubator functions to provide an environment that resembles the womb for premature babies or infants in need of care. To achieve optimal results, it is crucial for the baby to remain in an incubator with stable conditions. In certain situations, babies often feel uncomfortable and express their discomfort by crying. This discomfort can be addressed by using a swinging motion. By swinging, the baby will feel familiar with the movement since they frequently experienced it while in the womb. This research utilize a fuzzy logic control system with the frequency and intensity/level of the baby's cries as input and a PWM signal that drives the mechanical swing and an LCD indicator as output. The fuzzy logic control employed is the Mamdani method, consisting of fuzzification, rule base, and defuzzification stages. The fuzzification method used is the min-max method, while the defuzzification method employs the Mean of Maximum method. Based on the research results, the device is capable of identifying the baby's crying sound based on frequency (The range is around 250-1000 for normal and 100-2000 for hyperphonation) and intensity/level of cries in an environment with an ideal noise level for babies (in this case, a healthcare facility with a noise level of 55-65 dB). It then controls the motor to initiate the swing at various speeds and provides information on the LCD display. Keywords--- Craddle, Fuzzy, Cry, Infant, Frequecy, desiBell, Automatic.